Gender Identity and Sexual Orientation in Islamic Students at Salafiyah Islamic Boarding School Situbondo - Fitrio deviantony; Emi wuri wuryaningsih; Nindy arum setianing putri (Faculty of Nursing, Universitas Jember, 2021)
Background: The experience of adolescents related to sexuality and problems related to the lack of knowledge in understanding sexual identity will lead these adolescents to sexually deviant behavior Purpose: This study aimed to determine adolescents' characteristics in understanding gender and determine the orientation of adolescents related to sexual attraction in the Salafiyah Sukorejo Islamic school. Methods: This study used an observational analytic approach, with many respondents, as many as 478 students in Salafiyah Islamic schools. The sampling technique in this study used a simple random sampling technique. This study uses the Kinsey scale research instrument with a Cronbach's Alpha value of 0.929 and uses the Bem Sex Role Inventory instrument with a Cronbach's Alpha value of 0.868 Results: This study indicates that most students have a heterosexual type of sexual orientation, namely 96.3%, and the sexual identity of the majority of students, namely gender androgyny, as much as 43.9%. Conclusion: %. From the data above, this problem needs to be addressed further, such as early detection, assessment of sexual orientation, and prevention efforts related to sexual problems, which are useful for minimizing the occurrence of deviations in sexual orientation and gender identity in adolescent students